Ticagrelor and thrombolysis in myocardial infarction: what does the TREAT study change? - O. V. Averkov; V. I. Vechorko (Российский кардиологический журнал, 2018)
Primary percutaneous intervention (PCI) is a preferable reperfusion method in patients with STEMI. If on-time PCI is not possible, pharmacoinvasive approach is recommended that includes urgent systemic thrombolysis. Regardless the broad usage of ticagrelor in MI patients, its safety in combination with thrombolysis (first 24 hours from STEMI onset) before the year 2018 was unknown. In the TREAT study the patients 18-75 year old with STEMI (symptom onset within 24 hours), received thrombolytic drug, were randomized to ticagrelor or clopidogrel group. In 30 days from randomization it was shown that hemorrhagic safety of ticagrelor, at the level of major bleedings, was non-inferior than of clopidogrel. Therefore the TREAT study results, together with PLATO, make it to widen the indications for ticagrelor (and shift from clopidogrel) within first 24 hours of MI onset in patients received thrombolysis as a method of primary reperfusion.